Preventing Damage Limitation: Targeting DNA-PKcs and DNA Double-Strand Break Repair Pathways for Ovarian Cancer Therapy - Dungl, Daniela A.; Maginn, Elaina N.; Stronach, Euan A. (Frontiers in Oncology, 2015)
Platinum-based chemotherapy is the cornerstone of ovarian cancer treatment, and its efficacy is dependent on the generation of DNA damage, with subsequent induction of apoptosis. Inappropriate or aberrant activation of the DNA damage response network is are associated with resistance to platinum, and defects in DNA repair pathways play critical roles in determining patient response to chemotherapy. In ovarian cancer, tumour cell defects in homologous recombination - a repair pathway activated in response to DNA double strand breaks (DSB) - are most commonly associated with platinum sensitive disease. However, despite initial sensitivity, the emergence of resistance is frequent. Here, we review strategies for directly interfering with DNA repair pathways, with particular focus on direct inhibition of non-homologous end joining (NHEJ), another DSB repair pathway. DNA-PKcs is a core component of NHEJ and it has shown considerable promise as a chemosensitization target in numerous cancer types, including ovarian cancer where it functions to promote platinum-induced survival signalling, via AKT activation. The development of pharmacological inhibitors of DNA-PKcs is on-going, and clinic-ready agents offer real hope to patients with chemoresistant disease.